2014
DOI: 10.1097/01.tp.0000442775.46133.38
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Flk-1+Sca-1- Mesenchymal Stem Cells

Abstract: Flk-1Sca-1 bMSCs have stem cell properties and can efficiently ameliorate the GVHD associated with allogeneic bone marrow transplantation in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Five studies reported that animals were randomly assigned to an MSC or control group [ 13 , 19 , 33 , 38 , 44 ], and four studies indicated that the assessors were blinded to outcomes [ 15 , 45 , 53 , 58 ]. The majority of the included studies reported compliance with animal welfare requirements and conflict of interest statements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies reported that animals were randomly assigned to an MSC or control group [ 13 , 19 , 33 , 38 , 44 ], and four studies indicated that the assessors were blinded to outcomes [ 15 , 45 , 53 , 58 ]. The majority of the included studies reported compliance with animal welfare requirements and conflict of interest statements.…”
Section: Resultsmentioning
confidence: 99%
“…There was significant heterogeneity among the studies (I 2 = 66.1%, P = 2.12×10 −18 ) (Figure 1 ). In addition, 29 studies involving 41 comparisons examined the effect of MSCs on aGVHD-associated clinical scores [ 14 , 15 , 17 , 19 , 20 , 22 , 24 , 27 , 28 , 33 , 34 , 36 39 , 42 , 44 , 46 , 47 , 49 52 , 55 , 57 59 , 61 , 62 ]. The pooled analysis indicated that aGVHD-associated clinical scores were significantly lower in the MSC groups than in the control groups (SMD = −3.60, 95% CI −4.43 to −2.76, P = 3.61×10 −17 ) (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%